Strength performance of banana fiber ash mortar - Khairul Rizal, Suhaimi (2015)
In the history of the construction industry, mortars have been used for centuries to place masonry units more rapidly together. It is important for mortars to have the same basic characteristics as concrete in order for it to protect the units that it binds. Nowadays, mortars are being modified to produce mortars with improved properties such as better strength and workability. This research was conducted to determine the optimum cycle burning process and strength of mortar to produce good cementitious material by using banana fiber ash. Agriculture waste material can help to increase the strength of mortar. The source of natural fiber are found in plant and they are readily environmental friendly and cheap. In addition, natural fiber ash has an excellent potential to improve the performance of mortar. In this study, compressive strength test was conducted to know the strength of mortar with three different cycle burning process. Banana trunk is cut layer by layer and burn in furnace with three different cycle that is 1 cycle, 2 cycle, and 3 cycle at 500°C. A total of 27 cubes with 50 mm ×50 mm × 50 mm were used to determine the strength of mortar using banana fiber ash. All this specimens is cure for 7 days, 14 days and 28 days using water curing method. 2% of banana fiber ash was replaced with cement by weight. The materials use in this study was banana fiber ash, sand, cement and water. The result analysis shows, The highest number of cycle burning obtain in this research was by burned banana ash with 3 cycle at 500C. while 1 cycle is the lowest when the mortar was curing for 28 days. The highest the number of cycle burning process the higher the strength of mortar can be obtained.